(untitled) (Proceedings of International Educators Conference, 2024)
This scientific article explores the strategies and methods for enhancing the teaching methodology in the field of biopharmacy science. The ever-evolving nature of biopharmaceuticals demands an adaptable and innovative approach to education. This article discusses key areas of improvement, including the integration of modern technologies, hands-on practical experiences, individualized learning, industry collaboration, and the incorporation of interdisciplinary perspectives.